Effect of Arbuscular Mycorrhizal Fungi on Germination, Nodulation and Sporulation of Lentil (Lens culinaris) at Different NaCl Levels (Bangladesh Journal of Microbiology, 2019)
A pot experiment was carried out in the nethouse of Soil Science Division, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur during 2014-2015 through 2015-2016. The design of the experiment was factorial randomized completely block design with 4 replications. The objectives of the study were to evaluate the potential of Arbuscular mycorrhization (AM) on the germination, nodulation and sporulation of lentil treated with different concentration of NaCl. Five NaCl treatments (0, 1, 2, 3 and 4%) possessed NaCl level as the first factor that were treated with soils before sowing of lentil seeds pivotal pulse crop in Bangladesh. The second factor consists of mycorrhizal and nonmycorrhizal treatments. Mycorrhizal plants showed better performance in terms of germination (%), nodule number, nodule weight, spore population/100 g soil and root colonization (%) than non-mycorrhizal plants. With increasing NaCl concentration, germination (%), nodule number, nodule weight, spore population/100 g soil and root colonization (%) in the rhizosphere soil, decreased significantly (p